2011
DOI: 10.3727/152599511x13175676722483
|View full text |Cite
|
Sign up to set email alerts
|

Eliciting the Dynamics of Leading a Sustainable Event: Key Informant Responses

Abstract: Within the event management literature relating to network development and festival sustainability there is a paucity of research that analyzes the perception of festival sustainability by festival leaders. After an initial review of the context of sustainability, network theory, and an identification of the changing set of competencies for effective leadership, an exploratory and explanatory investigation is made to elicit and identify the critical factors that key informant festival leaders associate with su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…For event planners and directors -who will continue to have a myriad of social, economic and political stakeholder responsibility (Ensor et al 2011;Moital et al 2013), the capacity to involve representatives in scenario thinking will be increasingly important and may aid sustainable development (Cavagnaro et al 2012). The involvement of specialist researchers and facilitators will equally be vital.…”
Section: Implication Of Researchmentioning
confidence: 99%
“…For event planners and directors -who will continue to have a myriad of social, economic and political stakeholder responsibility (Ensor et al 2011;Moital et al 2013), the capacity to involve representatives in scenario thinking will be increasingly important and may aid sustainable development (Cavagnaro et al 2012). The involvement of specialist researchers and facilitators will equally be vital.…”
Section: Implication Of Researchmentioning
confidence: 99%
“…Kruger and Saayman (2012) hold that a "sustainable" festival is a festival that can remain competitive and successful over the long term. Employing a repertory grid method, Ensor et al (2011) conducted in-depth interviews with elite festival directors in order to capture their perceptions of festival sustainability. In their exploratory and explanatory study they found that the majority of festival leaders interpreted sustainability as a matter of a festival's ability to survive, rather than any environmental concern.…”
Section: Sustainability and The Festivalmentioning
confidence: 99%
“…In the field of event practice, an increasing number of music festival organisers, worldwide, are currently claiming that they can recognise and, essentially, address the potential negative externalities of their events by embedding the notion of "sustainability" into the management of such festivals. By calling attention to their "sustainability" credentials, they either label their festivals as "sustainable" or emphatically promote the events' contribution to "sustainability" (Ensor, Robertson, & Ali-Knight, 2011;Quinn, 2006;Raj & Vingali, 2010). Sustainability, however, is a discursive notion, which lacks a single, universal definition.…”
mentioning
confidence: 99%
“…In their exploratory research comprising depth interviews with festival directors from the UK and Australia, Ensor, Robertson and Ali-Knight (2011) found that leaders gave environmental and social sustainability a much lower value than their other managerial goals. Similarly, Mair (2011) reflects on the failure of managers of business events to address environmental issues (most particularly their contribution to global warming).…”
Section: Encourage Staff To Develop Creative and Innovative Approachementioning
confidence: 99%
“…It is important that creativity and innovation are seen as separate but related elements. So while creativity relates more particularly to the generation of ideas (Berridge, 2010), innovation is the process of their application (Ensor, Cottam, & Band, 2001;Ensor et al 2011). This to say that together they are about forming ideas, then designing applications and testing and applying them in the context in which they work.…”
Section: Encourage Staff To Develop Creative and Innovative Approachementioning
confidence: 99%